1996
DOI: 10.1007/s004649900150
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic anatomical (hepatic) left lateral segmentectomy—technical aspects

Abstract: Laparoscopic liver surgery is a tremendous challenge. The authors report a left liver lobectomy and removal by a total laparoscopic approach. Anatomical left lateral laparoscopic segmentectomy was performed on a woman who had a symptomatic hepatic adenoma. The patient was discharged after an uncomplicated postoperative recovery; the hospital stay and convalescence period were very short. The cosmetic result was good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 0 publications
1
64
0
4
Order By: Relevance
“…Azagra et al [8] reported the first LLLS more than 10 years ago, but it was a further 7 years until Lesurtel et al [4] reported in a case-control study their results in 18 patients treated with LLLS and compared to open left lateral sectionectomy in 20 patients; LLLS was associated with a longer operative time (202 vs. 145 min, p < 0.01), a longer portal clamping (39 vs. 23 min, p < 0.05) but with less blood loss (236 vs. 429 ml, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azagra et al [8] reported the first LLLS more than 10 years ago, but it was a further 7 years until Lesurtel et al [4] reported in a case-control study their results in 18 patients treated with LLLS and compared to open left lateral sectionectomy in 20 patients; LLLS was associated with a longer operative time (202 vs. 145 min, p < 0.01), a longer portal clamping (39 vs. 23 min, p < 0.05) but with less blood loss (236 vs. 429 ml, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic left lateral sectionectomy (LLLS) is considered the most suitable anatomical liver resection to be performed laparoscopically [4,5,6] and many would anticipate that laparoscopy will be the gold standard approach for the resection of lesions in the left lateral segment. LLLS is seen as the most suitable procedure to perform during the early part of the learning curve to gain experience before progressing to major resections such as left and right lobectomies [4,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopy has fundamentally changed general and particularly upper gastrointestinal surgery since its inception in the late 1980s. 1 Gradually this approach has been applied to a wider range of operations and now many complex procedures initially beyond the skill of laparoscopists are being successfully completed. [2][3][4] Liver resection is one area of recent development, and we report here our initial experience in performing laparoscopic liver resections.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the laparoscopic approach was adopted for wedge resection and left lateral sectionectomy, and only more recently it has been shown to be feasible and safe for major hepatectomy [12,13,14,15,16]. The majority of laparoscopic resections were originally performed for benign lesions [6,7].…”
Section: Introductionmentioning
confidence: 99%